Factors Associated with Long-Term Sickness Absence Due to Mental Disorders: A Cohort Study of 7.112 Patients during the Spanish Economic Crisis - Real, Eva; Jover, Lluís; Verdaguer, Ricard; Griera, Antoni; Segalàs, Cinto; Alonso, Pino; Contreras, Fernando; Arteman, Antoni; Menchón, José M. (PLOS ONE, 2016)
Background Mental health problems are very common and often lead to prolonged sickness absence, having serious economic repercussions for most European countries. Periods of economic crisis are important social phenomena that are assumed to increase sickness absence due to mental disorders, although research on this topic remains scarce. The aim of this study was to gather data on long-term sickness absence (and relapse) due to mental disorders in Spain during a period of considerable socio-economic crisis. Methods Relationships were analyzed (using chi-squared tests and multivariate modelling via binary logistic regression) between clinical, social/employment-related and demographic factors associated and long-term sickness absence (>60 consecutive days) due to mental disorders in a cohort of 7112 Spanish patients during the period 2008–2012. Results Older age, severe mental disorders, being self-employed, having a non-permanent contract, and working in the real estate and construction sector were associated with an increased probability of long-term sickness absence (gender had a mediating role with respect to some of these variables). Relapses were associated with short-term sick leave (return to work due to ‘improvement’) and with working in the transport sector and public administration. Conclusions Aside from medical factors, other social/employment-related and demographic factors have a significant influence on the duration of sickness absence due to mental disorders.